KEDUDUKAN DANA ALOKASI UMUM(DAU) DALAM HUBUNGAN ANTARA PUSAT DAN DAERAH BERDASARKAN ASAS OTONOMI - Yuswanto, Yuswanto (Lampung University)
As a fiscal policy within the framework of regional autonomy, the allocation of DAU is an act that very important. It was meant to address financing capability gap between regions. The reason is because the DAU is the largest component of balance funds, namely the lack of 26% of the net domestic income in the state budget the amount of DAU scheme is not limiting, because it can only grow with the size of the authority delegated to the regions. DAU legal standing as a regional income in the financial relationship between the center and the regions based on the principle of autonomy is as a subsidy coming from the state revenue in the state budget that is allocated to local revenue in the budget based on fiscal decentralization.Â Keywords: General Allocation Fund, autonomy, regional autonomy